Proteins derived from Bombyx batryticatus utilizing variable ultrasound powers: Evaluation of structural attributes, functional characteristics, and antioxidant capacities - Jing-ya Wang; Xi Peng; Qiao-Ling Deng; Zhi-Kun Wang; Kui-Xu Gao; Yao Wang; Yu-jie Liu; Mei-bian Hu (Ultrasonics Sonochemistry)
The current investigation evaluated the impact of diverse ultrasound power levels (0, 120, 200, 320, 400, and 520 W) on the structural, functional, and antioxidant potentials of proteins derived from Bombyx batryticatus (PBB). Findings indicated a marked increase in the yield of PBB via ultrasonic treatment at the appropriate ultrasound power (UP), accompanied by a diminished β-sheet content and an augmented proportion of α-helix and β-turn conformations. Furthermore, ultrasound extraction (UAE) at the appropriate UP broke down PBB into small and evenly dispersed fragments, and it also reshaped disordered PBB aggregates into a more regular, dispersed, and ordered arrangement. Also, it favorably modulated the functional properties of PBB, with notable improvements in solubility, water-holding capacity, emulsification properties, and emulsion stability. Antioxidant capabilities of PBB were also potentiated by ultrasound treatment, reaching optimal values for 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) (92.52 %), 1,1-diphenyl-2-picrylhydrazyl (DPPH) (89.33 %), hydroxyl (90.34 %) radical scavenging activity, and reducing power (1.61) at the UP of 400 W. UAE increased contents of hydrophobic amino acids, expanded the surface contact area, and exposed more binding sites for free radicals, thereby enhancing the antioxidant activity of PBB. These findings are expected to expand the further utilization of PBB in pharmaceutical sectors, cosmetics or food industry, and also provide new ideas for studying other activities of PBB.